Constitutive model of viscoelastic dynamic damage for the material of gas obturator in modular-charge howitzer - Zhonggang Li; Longmiao Chen; Yifan Li; Yufeng Jia; Quan Zhang (Defence Technology, 2024)
In order to investigate the mechanical response behavior of the gas obturator of the breech mechanism, made of polychloroprene rubber (PCR), uniaxial compression experiments were carried out by using a universal testing machine and a split Hopkinson pressure bar (SHPB), obtaining stress-strain responses at different temperatures and strain rates. The results revealed that, in comparison to other polymers, the gas obturator material exhibited inconspicuous strain softening and hardening effects; meanwhile, the mechanical response was more affected by the strain rate than by temperature. Subsequently, a succinct viscoelastic damage constitutive model was developed based on the ZWT model, including ten undetermined parameters, formulated with incorporating three parallel components to capture the viscoelastic response at high strain rate and further enhanced by integrating a three-parameter Weibull function to describe the damage. Compared to the ZWT model, the modified model could effectively describe the mechanical response behavior of the gas obturator material at high strain rates. This research laid a theoretical foundation for further investigation into the influence of chamber sealing issues on artillery firing.